CRISPR-Cas9 gene editing and its therapeutic applications: A literature review (Research, Society and Development, 2024)
The CRISPR-Cas9 technology has revolutionized biotechnology and medicine, offering new possibilities for the treatment of genetic and infectious diseases. This study aims to review the literature on the therapeutic applications of CRISPR-Cas9, highlighting advances, challenges, and future perspectives. The methodology used was a narrative literature review, with research conducted in the databases Google Scholar, LILACS, and SCIELO, covering articles published between 2000 and 2024 in Portuguese, English, and Spanish. The results indicate that CRISPR-Cas9 has shown great potential in preclinical and clinical studies. In animal models, the technology was effective in correcting genetic mutations responsible for diseases such as Duchenne muscular dystrophy and type I tyrosinemia. Initial clinical studies also demonstrated success in modifying T cells to treat hematological cancers and viral infections such as HIV. However, significant challenges remain, including the need to improve the specificity of genetic editing and delivery efficiency, as well as addressing ethical and safety issues. The conclusion highlights that despite the challenges, CRISPR-Cas9 has the potential to transform medicine and significantly improve patients' quality of life. Continuous research and interdisciplinary collaboration are essential to overcome these challenges. Proper regulation and effective communication with the public are also crucial to ensure that CRISPR-Cas9-based therapies are developed and implemented safely and ethically. With these efforts, CRISPR-Cas9 can lead to significant advances in human health, providing more effective and personalized treatments.